Antiproliferative and Antimicrobial Activities of Secondary Metabolites and Phylogenetic Study of Endophytic Trichoderma Species From Vinca Plants - Leylaie, Sahar; Zafari, Doustmorad (Frontiers in Microbiology, 2018)
Endophytic fungi have been recognized as a potential source of bioactive secondary metabolites. The endophytic Trichoderma species were isolated from Vinca plants (Vinca major,Vinca herbacea and Vinca minor), found in Iran and screened for antimicrobial and anti-proliferative activity. Based on morphological and phylogenetic analyses, four fungal species were identified: T. asperellum, T. brevicompactum, T. koningiopsis, and T. longibrachiatum. In addition, endophytic fungi bioactivity of methanol and ethyl acetate extracts (7.8–250 µgml-1) were assessed against a panel of pathogenic fungi and bacteria and IC80 was calculated. Data showed that both methanol and ethyl acetate extracts from all endophytic isolates had significant cytotoxic effects against the model target fungus Pyricularia oryzae. Further research indicated that they had significant antimicrobial bioactivity against the human pathogenic bacteria Staphylococcus aureus and Escherichia coli, and plant pathogenic bacteria Ralstonia solanacearum and Clavibacter michiganensisas well. According to the bioactivity results, crude ethyl acetate extract of T. konijiopsis VM115 isolate was determined for TLC and GC-MS analysis. An antifungal compound was isolated from ethyl acetate extract of T .konijiopsis VM115 based on bioassay guided fractionation. The spectroscopic data showed that the compound was trichodermin, which exhibited strong fungicidal effects against P. oryzae, Aspergillus fumigatus and Botrytis cinera with MICs of 31.25 µg ml-1 through in vitro antifungal tests. GC-MS analysis identified six classes of volatile compound produced by T. konijiopsis VM115 (alcohols, esters, pyrones (lactones), acids, furanes and lipids). 6-n-pentyl-6H-pyran-2-one(6PP) was identified as one of the most abundant metabolites in this research.These results indicate that the fungal endophytes from Vinca plants had antibacterial and cytotoxic activities; evidence that endophytes are a good source of biological activity and compounds. This work is the first report of Trichodermin production by T. konijiopsis species.